In Silico Studies on Fungal Metabolite against Skin Cancer Protein (4, 5-Diarylisoxazole HSP90 Chaperone). (6th September 2012) - Kandasamy, Saravanakumar; Sahu, Sunil Kumar; Kandasamy, Kathiresan
Abstract : This work was to find out the dominant secondary metabolites derived from the fungus Trichoderma and to test them against skin cancer protein. The metabolites were extracted in 80% methanol from the fungal biomass of Trichoderma isolated from mangrove sediment. The crude methanol extract was purified and analysed for the secondary metabolites by GC-MS. Three predominant compounds (heptadecanoic acid, 16 methyl-, methyl ester; 9, 12-octadecadienoic acid; cis-9-octadecenoic acid) identified in the extracts were screened against the skin cancer protein (Hsp90) by in-silico docking method. Of the compounds, heptadecanoic acid, 16 methyl, methyl ester was the most potent having the docking score of- 11.4592  Kcal/mol. This value was better than the standard drug "dyclonine". This work recommends the heptadecanoic acid, 16 methyl, methyl ester for further in vitro and in vivo studies towards its development as anticancer drug.